SPECIFICITY OF THE LEARNING PROCESS IN THE OPEN VIRTUAL LEARNING ENVIRONMENTS (VLE) - Nataliya B. Strekalova (Moscow Polytechnic University, 2016)
The article discusses the specificity of the learning process that is performed in an open e0 learning environment. An open virtual learning environment (VLE) is treated as an education systemof a special kind. Special attention is made on an open nature of VLE.